Drug monitoring of 5-fluorouracil: in vivo 19F NMR study during 5-FU chemotherapy in patients with metastases of colorectal adenocarcinoma - Schlemmer, Heinz-Peter; Bachert, Peter; Semmler, Wolfhard; Hohenberger, Peter; Schlag, Peter M.; Lorenz, Walter Josef; Kaick, Gerhard van (Magnetic resonance imaging, 1994)
The metabolism of 5-fluorouracil (5-FU) is complex and the reason for the low response rate of tumor patients to 5-FU is currently unknown. The aim of this study was to evaluate whether spectral parameters obtained noninvasively by in vivo 19F nuclear magnetic resonance (NMR) spectroscopy can be used to assess individual response to 5-FU chemotherapy. Eighteen patients with metastases of colorectal carcinoma treated with 5-FU were examined by 19F NMR at 1.5 T. The NMR signal intensity versus time curves were observed for the cytostatic and its catabolite α-fluoro-β-alanine (FBAL). Clinical response to treatment was monitored by CTMR imaging of the liver and carcinoembryonic antigen (CEA) levels in the serum. 5-FU levels observed in IV-treated patients correlate with volumes of metastases in the liver region examined with the 19F NMR coil (k = 0.77, p < .0001). 5-FU levels in patients at their initial 5-FU chemotherapy were related with clinical response determined after three cycles of treatment. In the group of patients with extensive liver involvement and IV treatment, responders (n = 3) had enhanced 5-FU levels compared to nonresponders (n = 3). FBAL data indicate an apparent saturation of 5-FU catabolism in the liver for 5-FU doses > 1 g infused during 10 min. Mean absolute concentrations of FBAL were about 1 μmol per gram liver tissue. 19F NMR spectroscopy could be used to guide dose escalation schemes or to assess the modulation of 5-FU metabolism by other drugs in combined chemotherapy.